Towards a Chinese Conception of Adolescent Development in a Migration Context - Ching-man Lam (The Scientific World Journal)
Although there are many well-known theories of adolescent development in the West, there is a notable lack of theory with empirical support to understand the process and outcome of Chinese adolescent development. This paper attempts to advance a Chinese conception of adolescent development in a migration context. A qualitative study approach was used to explore the experiences and views of 19 Chinese-Canadian adolescents from Hong Kong and ten of their parents. The findings indicate that parents and adolescents co-construct the dominant theme of “covert parental control” in the adolescent development process, and the concept of “self in relational networks” as the adolescent development outcome. Based on the developmental experiences of these Chinese-Canadian adolescents, a culturally sensitive model of Chinese adolescent development is proposed. This model incorporates culture and migration as two essential components of the framework for a theory regarding Chinese adolescent development. It acknowledges the experience of Chinese-Canadian immigrants, takes account of the participants' personal meanings, and incorporates the indigenous Chinese cultural concepts of bao (reciprocity), guan (guidance), and guanxi (relationship).